Leadership Development and School Transformation in Underserved South African Schools: A Phenomenological Study of the Dinaledi STP - Elona Nobukhosi Ndlovu; Patrick Ebewo; Knowledge Shumba; Mpilwenhle Nomvuyo Ndlovu; Tendai Makwara (Universitas Majalengka, 2026)
Leadership development in underserved educational contexts requires approaches that go beyond principal-centric training to bolster collective instructional capacity. This study investigates the Dinaledi School Transformation Programme (STP), an extensive year-long leadership development initiative implemented across six underserved South African schools. Guided by frameworks of transformational, constructive developmental, and distributed leadership, the research adopts a phenomenologically informed instrumental case study methodology to explore how participation influenced the leadership practices, organisational culture, and perceptions of contextual constraints among School Management Team (SMT) members. Semi-structured interviews were conducted with 12 SMT members, including principals, deputy principals, and departmental heads, and analysed using reflexive thematic analysis. Participants reported shifts from hierarchical, compliance-driven leadership toward more relational and instructionally engaged practices. Their narratives indicated improved collaboration, a clearer shared vision, enhanced support for teachers, and more structured stakeholder engagement. Nonetheless, challenges such as administrative overload, resource scarcity, and resistance to change moderated the sustainability of these developments. The findings underscore the importance of team-based, embedded leadership development and highlight the influence of structural conditions on instructional transformation.